2020
DOI: 10.1136/postgradmedj-2020-138822
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Orthopaedic Teaching programme for Students (COTS)

Abstract: IntroductionThere is a huge variation in the depth and breadth of content taught regarding orthopaedic examinations. Undergraduate students are often confused by the variability in examination teaching, therefore increasing concerns for upcoming objectively structured clinical examinations (OSCEs). Doctors, despite being expected to teach, rarely receive formal preparation, with only a handful of institutions providing necessary training. The Clinical Orthopaedic Teaching programme for Students (COTS) was desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…This has led to different aspects of trauma being taught between medical schools; indeed, our finding that 65.3% of graduates were dissatisfied with their broader trauma curriculum is in line with a study which found that most were also dissatisfied with T+O teaching specifically 7. While student-led societies and local clinicians have developed programmes to mitigate the deficiencies in undergraduate teaching,25–28 these initiatives vary between universities and there is a lack of standardised opportunities across the UK 27 28. Furthermore, where many believe that the medical school curriculum is overcrowded, with it being difficult to incorporate additional time to be solely dedicated to trauma teaching, and this additional time in trauma may detract from other specialties, most of our cohort stated they would have benefited from additional trauma teaching (89.2%) and that it would be useful to have a short course in trauma (93.7%), supplementary to medical school teaching.…”
Section: Discussionsupporting
confidence: 75%
“…This has led to different aspects of trauma being taught between medical schools; indeed, our finding that 65.3% of graduates were dissatisfied with their broader trauma curriculum is in line with a study which found that most were also dissatisfied with T+O teaching specifically 7. While student-led societies and local clinicians have developed programmes to mitigate the deficiencies in undergraduate teaching,25–28 these initiatives vary between universities and there is a lack of standardised opportunities across the UK 27 28. Furthermore, where many believe that the medical school curriculum is overcrowded, with it being difficult to incorporate additional time to be solely dedicated to trauma teaching, and this additional time in trauma may detract from other specialties, most of our cohort stated they would have benefited from additional trauma teaching (89.2%) and that it would be useful to have a short course in trauma (93.7%), supplementary to medical school teaching.…”
Section: Discussionsupporting
confidence: 75%
“…Our online teaching programme surpassed other in-person37 39 and online31 46 specialty-specific teaching programmes, in terms of recruitment. With our unique combination of our national society and teaching programme, we achieved a wide national outreach of 3743 student responses (92.2% of attendees) from 35 medical schools.…”
Section: Discussionmentioning
confidence: 94%
“…All data from feedback forms were collected and collated on an Excel Spreadsheet and analysed using SPSS Statistics (IBM, SPSS, V.25). The Wilcoxon matched pairs signed rank test was used to compare MCQ scores prior and post teaching session, with p<0.05*, p<0.01** and p<0.001*** considered as statistically significant, in accordance with current literature 31 37 40. Results are presented as the mean±SD, using Graphpad Prism V.5 software (Graphpad, Sand Diego, California, USA).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations